2010
DOI: 10.1007/s10457-010-9278-y
|View full text |Cite
|
Sign up to set email alerts
|

Can oil palm plantations become bird friendly?

Abstract: Despite the increasing claims that structural complexity in agroforestry plantations is a key variable for enhancing bird biodiversity, few studies have experimentally manipulated the understory component of structural complexity. Here, we examined the impact of removing understory vegetation from oil palm plantations on the richness and abundance of birds in eastern Guatemala, testing if bird richness and abundance are positively affected by the presence of understory vegetation. Oil palm plantations with und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 27 publications
5
43
0
3
Order By: Relevance
“…Understory of plantations seems a key factor that could increase the occurrence of native fauna in plantations. We found that stands of Monterery pine with no or barely developed understory contained fewer species of medium‐sized mammals, which is consistent with Nájera and Simonetti's () finding that Guatemalan oil palm plantations with little understory support fewer bird species than stands with a well‐developed understory. That the experimental removal of understory reduced the use of such stands by mammals strongly suggests understory enhances the quality of plantations as habitat for native fauna, which in this case includes 2 vulnerable species, kodkod and Southern pudu.…”
Section: Discussionsupporting
confidence: 90%
“…Understory of plantations seems a key factor that could increase the occurrence of native fauna in plantations. We found that stands of Monterery pine with no or barely developed understory contained fewer species of medium‐sized mammals, which is consistent with Nájera and Simonetti's () finding that Guatemalan oil palm plantations with little understory support fewer bird species than stands with a well‐developed understory. That the experimental removal of understory reduced the use of such stands by mammals strongly suggests understory enhances the quality of plantations as habitat for native fauna, which in this case includes 2 vulnerable species, kodkod and Southern pudu.…”
Section: Discussionsupporting
confidence: 90%
“…Although it has been recognised that the maintenance of the understory vegetation can improve habitat quality within plantations by providing resources for mammals (Bellows et al 2001;Hartley 2002;Lindenmayer & Hobbs 2004), no experimental studies have addressed this issue at this time. Nájera and Simonetti (2010b) have demonstrated that the removal of the understory vegetation reduces bird diversity and abundance in oil palm plantations, but this kind of research is absent in the case of mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Understorey vegetation has been shown to be important in maintaining the abundance and richness of beetle assemblages in oil palm in Sabah [18] and of bird communities in Guatemalan oil palm [100]. Understorey vegetation can also be important in producing increased amounts of leaf litter in plantations, which can itself support a higher diversity and abundance of taxa [18].…”
Section: Methods For Conservation Of Biodiversity and Ecosystem Functmentioning
confidence: 99%